CHEMICAL COMPONENTS AND EFFECT ON STREPTOZOTOCIN INDUCED DIABETES OF BRIDELIA FERRUGINEA BENTH (EUPHORBIACEAE) ROOT BARK ETHYL ACETATE FRACTION. - BATOMAYENA BAKOMA,; BÉNÉDICTE BERKÉ,; KWASHIE EKLU-GADEGBEKU,; NICHOLAS MOORE, (International Journal of Pharma and Bio Sciences, 2015)
The root of Bridelia ferruginea is traditionally used as a treatment for type 2 diabetes. The objective of this study was to evaluate the effect of Bridelia ferruginea root bark ethyl acetate fractions (EA) on streptozotocin-induced diabetes and identify some chemical compounds. Ethyl acetate fraction (25 and 50 mg/kg/day) was administrated to streptozotocin-induced (60 mg/kg) diabetic mice for 3 weeks. Oral glucose tolerance test and biochemical parameters were estimated at the end of the study. Chemical composition of EA was analysed using HPLC/DAD/MS and HNMR. The level of fasting blood glucose, triglycerides (TG), total cholesterol (TC) insulin and glucose intolerance in streptozotocin-induced diabetic mice were significantly (P<0.01) reduced after daily oral administration of ethyl acetate fraction at the dose of 50mg/kg/day (EA50) for 21 days compared to diabetic control mice. EA25 showed only a significant (p<0. 01) reduction of TG. After chemical analysis, Epigallocatechin (EGC), Epigallocatechin gallate (EGCG) and derivates were identified from the ethyl acetate fraction of Bridelia ferruginea. In conclusion these catechins and derivates can be some antidiabetic compounds of this plant according to their properties in the literature.